Extraction of β-carotene from organic phase using ammonium based ionic liquids - Rajabi, M.S. (Elsevier B.V., 2017)
β-carotene, an important biomolecule from the carotenoid family with highly unsaturated heavy structure (C40H56) can be found in plenty of sea products, fruits and vegetables. This hydrocarbon with a noticeable antioxidant is known to be a valuable compound in food and pharmaceutical industries. The present study aimed to have a detailed probe on the capability of ammonium based Ionic liquids (ILs) to extract β-carotene from its model solvent, n-hexane. The work entails the screening of ILs by employing conductor-like screening model for real solvents (COSMO-RS) tool based on the numerical prediction of relationship between ILs structure and its extraction potential. The simulated results were then complemented experimentally. Besides, process conditions for β-carotene extraction from n-hexane; including IL water content, two-phase volumetric ratio (aqueous to organic) and extraction time were also optimized using response surface methodology (RSM) based on central composite design (CCD). The results indicate that tetramethylammonium and trimethylethylammonium based ILs with acetate anion exhibited potential extraction efficiency of 63.09 and 37.89 for β-carotene, respectively. Interestingly, ‘IL water content’ is found to be the most efficacious parameter in the extraction process while ‘time’ retained a nominal impact. In the promise of these findings, we firmly believe that this newly proposed method would open a new pathway for β-carotene extraction for numerous applications. © 2016